Hazard Identification of Liquefied Natural Gas (LNG) Transportation and Storage in DKI Jakarta Province - Sari Sekar Ningrum; Aidha Zulaika; Dody Guntama (CHEMICA: Jurnal Teknik Kimia, 2022)
LNG is an alternative fuel to replace diesel and gasoline. The use of LNG as a fuel has many advantages from various aspects. Besides having advantages, LNG also has disadvantages because it contains dangers in it. LNG is a volatile material that is easily flammable, which causes fires and explosions. Environmental Risk Assessment (ERA) is a systematic method used to measure the magnitude of the risk of a process and product that is a hazard to human health and ecology. By conducting an ERA, the risks and hazards of LNG are known. In carrying out the research, describing the LNG delivery system, identifying hazards in the event of LNG released from the carrier, making accident scenarios along with the outcome events that will occur, collecting data, calculating the frequency of accidents and their consequences, determining existing risks, and providing preventive actions, and mitigation. Hazard evaluation was determined using fault tree analysis (FTA) and event tree analysis (ETA). Based on identifying hazards to the storage and transportation of LNG, it is classified into category four and server (severe). Scenarios of releasing LNG into the environment in the process of transporting and storing LNG can be caused by several things, including external factors, failure in filling, and failure due to excess pressure so that it can cause fire pools/BLEVE events, cloud vapor explosions, flash fires, and cloud vapors. Based on the level of risk entered into, not tolerable action at the next opportunity.